Age‐related spontaneous lumbar intervertebral disc degeneration in a mouse model. Issue 1 (9th July 2017) - Ohnishi, Takashi; Sudo, Hideki; Tsujimoto, Takeru; Iwasaki, Norimasa
ABSTRACT: The pathogenesis of intervertebral disc degeneration is unclear, but it is a major cause of several spinal diseases. Animal models have historically provided an appropriate benchmark for understanding the human spine. However, there is little information about when intervertebral disc degeneration begins in the mouse or regarding the relationship between magnetic resonance imaging and histological findings. The aim for this study was to obtain information about age‐related spontaneous intervertebral disc degeneration in the mouse lumbar spine using magnetic resonance imaging and a histological score regarding when the intervertebral disc degeneration started and how rapidly it progressed, as well as how our histological score detected the degeneration. The magnetic resonance imaging index yielded a moderate correlation with our Age‐related model score. The Pfirrmann grade and magnetic resonance imaging index had moderate correlations with age. However, our Age‐related model score had a high correlation with age. Intervertebral disc level was not a significant variable for the severity of disc degeneration. Both Pfirrmann grade and the Age‐related model score were higher in the ≥14‐month‐old group than in the 6‐month‐old group. The present results indicated that mild but significant intervertebral disc degeneration occurred in 14‐month‐old mice, and the degree of degeneration progressed slowly, reaching a moderate to severe condition for 22‐month‐old mice. At least a 14‐month follow‐up is mandatory for evaluating spontaneous age‐related mouse intervertebral disc degeneration. The histological classification score can precisely detect the gradual progression of age‐related spontaneous intervertebral disc degeneration in the mouse lumbar spine, and is appropriate for evaluating it. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:224–232, 2018. Abstract : Our histological classification score (Age‐related model score) had a high correlation with age, and had a better correlation compared with those of Pfirrmann grade or magnetic resonance imaging index with age. Both Pfirrmann grade and Age‐related model score were higher in the ≥14‐month‐old group than in the 6‐month‐old group, indicating that mild but significant intervertebral disc degeneration occurred in 14‐month‐old mice. The degree of degeneration progressed slowly, reaching a moderate to severe condition for 22‐month‐old mice.